Argonne Pixel Tracking Telescope at the Fermilab Test Beam Facility. (1st November 2022) - Bhopatkar, V.; Benoit, M.; Dong, B.; Kiehn, M.; Lambert, J.; Metcalfe, J.; Muse, J.; Wilbern, D.
Abstract: The Argonne Pixel Tracking Telescope is installed at the Fermilab Test Beam Facility. The telescope consists of six planar n + -in-n silicon sensors with a pixel size of 250 × 50 μm 2 . The instrumentation of the telescope is described including the electrical and mechanical setups. A 120 GeV proton beam is used to evaluate the telescope performance using criteria such as cluster size, pixel tracking efficiency, and spatial resolution. The spatial resolution of the telescope is measured to be 72 μm × 13 μm and is consistent with the resolution determined from the simulation. This telescope will be used to test the performance of the various silicon pixel technology as well as to study the effects and the performance of the detectors after being irradiated.